(untitled) (AYUSHDHARA, 2024)
Background: For a women pregnancy is a pleasant life event marked by progressive anatomical, physiological, and biochemical changes that affect not only the reproductive organs but the entire body. Unfortunately In developing countries, nutrient deficiencies have made anemia a significant contributor to both mortality and morbidity. Objective: This study was carried out to know the effect of Dhatri louha with Draksha ghrita in Garbhini Pandu. Material and Methods: A patient aged 24 years suffering from anemia in pregnancy was selected. she was administered with Dhatri louha 500 mg twice daily and Draksha ghrita 10 ml twice daily before meal for the period of 60 days. Result: The study demonstrated a positive effect on the cardinal symptoms of Garbhini Pandu, along with improvements in Hb%, RBC count, PCV, MCH, MCHC, MCV, serum iron, and serum ferritin levels. Conclusion: This study has shown that the combined effect of both drugs results in leads to improved Agni, enhanced iron absorption, improved Haemoglobin, and alleviation of the signs and symptoms of Garbhini Pandu.